Direct somatic embryogenesis and plant regeneration in Garcinia indica Choiss - Thengane, Shubhada Ratnakar; Deodhar, Swapna R.; Bhosle, S. V.; Rawal, S. K. (Current Science, 2006)
Direct somatic embryogenesis without an intervening callus phase was induced from immature seeds of Gar- cinia indica Choiss. Woody plant medium supplemented with 6-benzyl amino purine (BAP) (4.44-22.19 mu m) alone or in combination with a-naphthaleneacetic acid (2.69 mu m) produces somatic embryos within a period of 2-3 weeks with 80% frequency. Embryo induction was observed all over the explant surface. Origin of the embryo was confirmed histologically from sub-epidermal layer of the seed. Maturation of these embryos was achieved after 12 weeks of culture on a medium containing BAP (16.08 mu m) in combination with indole-3-acetic acid (2.85-5.71 mu m) and/or kinetin (4.65 mu m). About 75% of the regenerated somatic embryos germinated into complete plantlets. The plantlets were acclimatized successfully with 92% survival in greenhouse.
Keywords: Garcinia indica; guttifereae; seeds; somatic embryos

Micropropagation of Indian laurel (Calophyllum inophyllum), a source of anti-HIV compounds - Thengane, Shubhada Ratnakar; Bhosle, S. V.; Deodhar, Swapna R.; Pawar, K. D.; Kulkarni, D. K. (Current Science, 2006)
An efficient protocol for in vitro micropropagtion of Calophyllum inophyllum (Linn.), an evergreen littoral tree, through multiple shoot formation from seed explants was developed. In vitro germination of the seeds was standardized on Woody Plant Medium (WPM) hormone free and/or supplemented with 6-benzylaminopurine (BAP; 2.22 mu M) and on half or full strength MS medium. Multiple shoot formation was achieved on WPM supplemented with BAP (2.22-44.00 mu M) and thidiazuron (TDZ; 0.91-4.54 mu M) from the decapitated seedling explants. The maximum multiple shoots, 20.9 per explant were induced on TDZ (0.91 mu M) after two subcultures. Elongated shoots of size > 4.0 cm were obtained on all media combinations with an average of 2.2-8.7 per explant. Elongation of the stunted shoots induced on BAP and TDZ was done on half strength WPM without any growth hormones. The elongated shoots on half WPM and/or full strength WPM supplemented with indole-3-butyric acid (2.46-24.60 mu M) alone or in combination with BAP (2.22 mu M) resulted in 52% rooting with 1-5 roots per rooted plant. The micropropagated plants were acclimatized successfully with 77% survival rate after five weeks. These plants were planted in the institute campus for ex situ conservation, where 72% plants are showing good growth and development.
Keywords: Calophyllum inophyllum; ex situ conservation; micropropagation; seed

Repetitive somatic embryogenesis and plant regeneration in Garcinia indica Choiss - Thengane, Shubhada Ratnakar; Deodhar, Swapna R.; Bhosle, S. V.; Rawal, S. K. (In Vitro Cellular & Developmental Biology-Plant, 2006)
Immature seeds of Garcinia indica Choiss. were excised from immature fruits and cultured on Lloyd and McCown (1980), woody plant medium (WPM) with different combinations of auxins and cytokinins. Somatic embryos were obtained on the media supplemented with 6-benzylaminopurine (BA; 2.2-22.1 mu M) alone or in combination with alpha-naphthalene acetic acid (NAA; 2.6 mu M) with 80% frequency within a period of 2-3 wk. Subculture of embryos on medium containing BA (16.0 mu M) supplemented with indole-3-acetic acid (IAA; 2.8-5.7 mu M) and/or kinetin (4.6 mu M) gave rise to clusters of secondary somatic embryos along with maturation of primary embryos. In subsequent subculture on hormone-free half-strength WPM, the embryo clusters germinated with an increase in the number of secondary somatic embryos. About 70% of somatic embryos germinated into complete plantlets, which were successfully established under greenhouse conditions.
Keywords: Garcinia indica; guttifereae; secondary somatic embryos; seeds; somatic embryos

De novo shoot regeneration from root cultures of garcinia indica choiss - Deodhar, Swapna R.; Thengane, R. J.; Thengane, Shubhada Ratnakar (Indian Journal of Experimental Biology, 2008)
Roots of plantlets of Garcinia indica when cultured for long time on half strength MS medium supplemented with BAP (0.44-2.22 mu M) showed production of de novo shoots. Roots attached to mother plant showed more number of shoots, while excised root segments produced lesser shoots. Shoots (0.5-0.8 cm) were transferred to elongation medium consisting of Woody Plant Medium (WPM) supplemented with BAP (4.44-22.69 mu M), IAA (5.71 mu M and kinetin (4.65 mu M). It was observed that shoot length increased to 1-2 cm. WPM medium supplemented with NAA (2.69-10.74 mu M) and IBA (4.90 mu M) induced rooting within 20-25 days. Using the present protocol, 20-25 plantlets could be regenerated from single root explant within 3 to 4 months. The protocol has potential for large scale production of elite plants.
Keywords: Garcinia indica; guttifereae; organogenesis; roots; shoots